2002
DOI: 10.1046/j.1440-6055.2002.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Colony structure and nest characteristics of European wasps, Vespula germanica (F.) (Hymenoptera: Vespidae), in Victoria, Australia

Abstract: European wasps, Vespula germanica , are common across southern and south-eastern Australia and have a negative impact upon urban areas, primary industries, and natural ecosystems. Aspects of colony structure and nest characteristics are examined for nests located in the ground and collected from urban and rural sites in Victoria during two summer-autumn field seasons (1996 and 2001). On average, nests were located 28 cm beneath the surface (range 5-58 cm). The average number of combs in the nest and the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…They are frequently excluded from biodiversity assessments; for example an evaluation of changes in species richness in metropolitan Adelaide was described recently using only vertebrate and vascular plant knowledge . Furthermore, existing urban invertebrate research has focused on obvious or charismatic species, such as butterflies (Brown and Freitas 2002;New and Sands 2002;Dover and Rowlingson 2004;Collier et al 2006) or pest species (epidemiology and economic/agricultural aspects) (Ali et al 1986;Wishart 1999;McIntyre 2000;Ward et al 2002;Hausmann et al 2004;Hwang and Turner 2005;Russell et al 2005). Research on Australia's urban invertebrates is particularly limited; temporal variation in assemblages is poorly understood and mechanisms driving arthropod distributions are unclear, as are the implications for their insectivorous predators (Garden et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They are frequently excluded from biodiversity assessments; for example an evaluation of changes in species richness in metropolitan Adelaide was described recently using only vertebrate and vascular plant knowledge . Furthermore, existing urban invertebrate research has focused on obvious or charismatic species, such as butterflies (Brown and Freitas 2002;New and Sands 2002;Dover and Rowlingson 2004;Collier et al 2006) or pest species (epidemiology and economic/agricultural aspects) (Ali et al 1986;Wishart 1999;McIntyre 2000;Ward et al 2002;Hausmann et al 2004;Hwang and Turner 2005;Russell et al 2005). Research on Australia's urban invertebrates is particularly limited; temporal variation in assemblages is poorly understood and mechanisms driving arthropod distributions are unclear, as are the implications for their insectivorous predators (Garden et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Donovan et al (1992) noted a general seasonal increase in numbers of combs in Christchurch, New Zealand, also observed in this study. However, Fordham et al (1991) in Manawatu, New Zealand, andWard et al (2002) in eastern Australia found a linear relationship between sampling date and number of combs present. When two of these studies examined nest size in terms of nest area, the results show the same pattern of linear increase with season (Donovan et al 1992;Ward et al 2002).…”
Section: Nest Sizementioning
confidence: 99%
“…These include numbers of comb layers (e.g. Fordham et al 1991;Donovan et al 1992;Ward et al 2002) and total area of combs (e.g. Donovan et al 1992;Ward et al 2002).…”
Section: Nest Sizementioning
confidence: 99%
See 2 more Smart Citations